Sosialisasi Pemasaran Digital Untuk Meningkatkan Penjualan Pada Ibu Ibu Kelurahan Curug Bojongsari Depok - Laura Komala; Pusporini Palupi Jamaludin; Elizabeth Tika Kristina; Paringsih Paringsih (Jurnal Informasi Pengabdian Masyarakat, 2024)
The aim of the Community Service Activities is to carry out one of the Tri Darmas of Higher Education which is carried out by lecturers and students at Pamulang University with the title "Digital Marketing Socialization to Increase Sales to Mothers in Kel. Bojongsari Waterfall, Depok”. In this socialization, residents still need better entrepreneurial management in business and have not utilized technology well. The method used to implement this PKM is a workshop or training. Where previously a direct observation stage was carried out first to find out the problems that arose at the service location. This socialization is used to provide an in-depth understanding of Community Service. It is hoped that the existence of higher education can contribute to the development of the application of science to society. The method used in community service is conveying material verbally. In this implementation, the material is by providing educational outreach to mothers in Kel. Curug in capturing business opportunities and implementing marketing strategies by utilizing smartphones as marketing media so that they can maintain their business and develop their business in the future. In the final training session participants were also given simple practices to support their ability to implement entrepreneurship in small businesses that are already running. To improve and ensure participants' ability to apply the material optimally, regular evaluation stages will be carried out by the team of lecturers and PKM teaching practitioners.